Impact of methods used to reconstitute tailings specimens on the liquefaction potential assessment of tailings dams - Corrêa,Mariana Martins (2019)
Abstract The aim of this research is to investigate the liquefaction susceptibility of silt sandy mining tailings by experimental laboratory techniques. The main aspect analyzed is how techniques of sample reconstitution impact the results obtained in static undrained triaxial tests. Different methods of sample preparation are reviewed, such as moist tamping (MT), air and water pluviation, and a newly developed one called the Slurry Deposition (SD) method. This research highlights the importance of the "fabric" or particle structural arrangement associated with the various specimen preparation techniques when liquefaction potential assessment is of concern. Two series of undrained static triaxial tests were performed on specimens prepared according to MT and with SD techniques on specimens in the loose and very loose state. Results have demonstrated that MT specimens have shown the whole spectrum of liquefaction resistance (total liquefaction, limited liquefaction, and no liquefaction) on increasing density, while the SD campaign has shown only liquefaction resistance even in the overlapping intermediate densities with the MT series, where the latter has shown liquefaction, although limited. This scientific study critically discusses the risk of taking laboratory results of replicated soil elements that may not correspond to the reality.